IMPLEMENTATION OF QUALITY MANAGEMENT SYSTEM ISO 9001:2008 IN MAN MODEL BUKITTINGGI - Novsia Rahim (Jurnal Bahana Manajemen Pendidikan, 2014)
The purpose of this research is to gain an overview of: (1) the implementation of ISO 9001:2008 Quality Management System in MAN Model Bukittinggi, (2) the factors that support the implementation of ISO 9001:2008 Quality Management System in MAN Model Bukittinggi, (3) implementation constraints of ISO 9001:2008 Quality Management System in MAN Model Bukittinggi, (4) the benefits of the implementation of ISO 9001:2008 Quality Management System in MAN Model Bukittinggi. This research was conducted at MAN Model Bukittinggi. This study used a descriptive research is. Data collection technique here using interview techniques, observation, and documentation The results showed: (1) ISO 9001:2008 system implementation at MAN Model Bukittinggi is good. (2) The factors that support the implementation of the ISO 9001:2008 system at MAN Model Bukittinggi namely (a) the awareness and commitment of the school community, (b) infrastructure (c) quality input, (d) human resources. (3) The factors that impede the implementation of the ISO 9001:2008 system are (1) lack of human resources in charge of special documenting ISO, (2) a sense of indifference, (3) workload. Implementation of the quality management system ISO 9001:2008 in Bukittinggi MAN Model will provide benefits such as: (a) In every activity and administrative system more organized and controlled, (b) more easily find the documents that are stored and tidier, (c) togetherness and cohesiveness in implementing a management system, (d) Schools are recognized as having international management system, (e) Trust by universities both domestically and abroad Keywords: Implementation, Quality Management System, ISO 9001:2008